Virtual Reality Sebagai Media Promosi Wisata Kuliner Halal Di Solo Baru Sukoharjo - Aisyah Mutia Dawis; Murhadi Murhadi; Rahmad Ardhani (Universitas Muhammadiyah Purworejo, 2023)
Nowadays technology is increasingly advanced and modern. Virtual Reality (VR) is starting to be used as a medium for promoting halal culinary tourism to be relevant and important. Virtual reality (VR) is a technology that allows users to interact with a digital environment that is created in such a way that it feels real. By using VR, potential travelers can experience eating at a halal restaurant or cafe in a more immersive and realistic way before they actually visit the place. In addition, VR can also be used to introduce the menu and promote the various halal culinary dishes available. With the use of virtual reality technology, tourists or the general public can easily identify which food places are halal clearly, because currently in Solo Baru Sukoharjo there are several places to eat that are not halal because they contain non-halal food ingredients that have begun to spread, besides that tourists can also experience halal culinary experiences directly and learn about the process of making and cleaning food that is explained in de-tail. This experience can be an added value that allows the promotion of halal culinary tourism to be more effective and efficient. Through this research, it is hoped that the promotion of halal culinary tourism in Solobaru Sukoharjo can become wider and reach more tourists.